Effects of Mesenchymal Stem Cells on Functions of Chimeric Antigen Receptor-Expressing T Lymphocytes and Natural Killer Cells - Vladislav Volarevic; Carl Randall Harrell; Aleksandar Arsenijevic; Valentin Djonov; Ana Volarevic (Cells)
Chimeric antigen receptor (CAR)-engineered immune cells, particularly CAR T lymphocytes and CAR natural killer (NK) cells, have revolutionized cancer immunotherapy. However, their therapeutic efficacy and safety can be influenced by the tumor microenvironment, particularly the presence of mesenchymal stem cells (MSCs). MSCs are immunomodulatory cells which can alter the function of tumor-infiltrated immune cells in both supportive and suppressive ways. Results obtained in recently conducted experimental studies demonstrate that MSCs modulate proliferation, cytotoxicity, cytokine production and anti-tumor activity in CAR-expressing immune cells in both a juxtacrine and a paracrine manner. While MSCs can enhance CAR cell viability and persistence through trophic support, they may also impair cytotoxic function and promote an immunosuppressive phenotype under certain conditions. Understanding the dualistic nature of MSCs in CAR-based immunotherapy for malignant diseases is critical for optimizing clinical outcomes. Additionally, MSCs may serve as vehicles for targeted delivery of immunomodulatory agents, and should be considered as active components in the design of next-generation CAR-based immunotherapies. Accordingly, in this review article we emphasize molecular and cellular mechanisms involved in MSC-dependent modulation of CAR-expressing immune cells, paving the way for more efficient CAR-based immunotherapy for malignant diseases.